2016
DOI: 10.1007/s10096-016-2790-x
|View full text |Cite
|
Sign up to set email alerts
|

Toxin A-negative toxin B-positive ribotype 017 Clostridium difficile is the dominant strain type in patients with diarrhoea attending tuberculosis hospitals in Cape Town, South Africa

Abstract: The molecular epidemiology of C. difficile strains causing disease in South Africa is currently unknown. Previously, multidrug resistant ribotype (RT)017 strains were those most commonly isolated from patients with diarrhoea attending Groote Schuur Hospital in Cape Town, South Africa. This larger study aimed to investigate the molecular epidemiology and antibiotic susceptibility profiles of C. difficile strains in the greater Cape Town and regional areas. C. difficile strains were isolated from patients with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 62 publications
2
21
0
Order By: Relevance
“…Less is known of the molecular epidemiology of C. difficile in South America, but RTs 027, 106, 012, 046, and 014/020 are reportedly the most common strains [31,33,34]. Similar to the current study, RT 017 (followed by RT 001) has also been found at high prevalence in South Africa [35], and in Ghana, Malawi, and Tanzania the few studies which performed molecular typing have shown a high prevalence of non-toxigenic strains [36,37], similar to reports from Southeast Asian countries [15].…”
Section: Discussionsupporting
confidence: 80%
“…Less is known of the molecular epidemiology of C. difficile in South America, but RTs 027, 106, 012, 046, and 014/020 are reportedly the most common strains [31,33,34]. Similar to the current study, RT 017 (followed by RT 001) has also been found at high prevalence in South Africa [35], and in Ghana, Malawi, and Tanzania the few studies which performed molecular typing have shown a high prevalence of non-toxigenic strains [36,37], similar to reports from Southeast Asian countries [15].…”
Section: Discussionsupporting
confidence: 80%
“…This included samples from both DS tuberculosis and MDR tuberculosis patients and contrasts with a concurrent set of isolates obtained from patients attending other hospitals in the Cape Town area (37% of strains resistant to rifampicin). 30 It is also higher than that observed for strains isolated from the general hospital population in Europe (0% – 63.64%). 42 Rifampicin is included as part of the standard DS tuberculosis treatment regimen and exposure to antibiotics belonging to this class has been associated with the development of resistance in C. difficile .…”
Section: Discussionmentioning
confidence: 75%
“…5,53 RT017 strains were also commonly isolated from other hospitals in Cape Town during the same time period, suggesting that these strains are circulating more broadly in the Cape Town patient population. 30,54 It is possible that the previous use of standalone enzyme immunoassay diagnostic tests that target toxin A alone allowed RT017 strains to proliferate undetected in the region, providing a reservoir of strains in the healthcare environment with the potential to cause outbreaks in susceptible patient populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations